Shwachman‐Diamond syndrome with clonal interstitial deletion of the long arm of chromosome 20 in bone marrow: haematological features, prognosis and genomic instability. (26th December 2018) - Valli, Roberto; Minelli, Antonella; Galbiati, Marta; D'Amico, Giovanna; Frattini, Annalisa; Montalbano, Giuseppe; Khan, Abdul W.; Porta, Giovanni; Millefanti, Giorgia; Olivieri, Carla; Cipolli, Marco; Cesaro, Simone; et al.
Summary: In Shwachman‐Diamond syndrome (SDS), deletion of the long arm of chromosome 20, del(20)(q), often acquired in bone marrow (BM), may imply a lower risk of developing myelodysplastic syndrome/acute myeloid leukaemia (MDS/AML), due to the loss of the EIF6 gene. The genes L3MBTL1 and SGK2, also on chromosome 20, are in a cluster of imprinted genes, and their loss implies dysregulation of BM function. We report here the results of array comparative genomic hybridization (a‐CGH) performed on BM DNA of six patients which confirmed the consistent loss of EIF6 gene. Interestingly, array single nucleotide polymorphisms (SNPs) showed copy neutral loss of heterozygosity for EIF6 region in cases without del(20)(q). No preferential parental origin of the deleted chromosome 20 was detected by microsatellite analysis in six SDS patients. Our patients showed a very mild haematological condition, and none evolved into BM aplasia or MDS/AML. We extend the benign prognostic significance of del(20)(q) and loss of EIF6 to the haematological features of these patients, consistently characterized by mild hypoplastic BM, no or mild neutropenia, anaemia and thrombocytopenia. Some odd results obtained in microsatellite and SNP‐array analysis demonstrate a peculiar genomic instability, in an attempt to improve BM function through the acquisition of the del(20)(q).